A good girl's guide to murder. [Series 1] [videorecording (DVD)] - Cogan, Poppy; Thomas, Ruby; Ibiroke, Ajoke; Myers, Emma, 2002-; Iqbal, Zain; Banks, Asha; Gohara, Raiko; Morgan-Collie, Jude; Margalith, Yali Topol; Al-Khudhairi, Yasmin; Ashton, Henry, 1991-; Woodcock, Carla; et al. (2025)
A closed murder case of five years. An a-grade student who won't let it go. Compulsive thriller based on Holly Jackson's hit novel and starring Emma Myers. Five years ago, popular student Andie Bell went missing from the tiny town of Little Kilton. Three days later, boyfriend Sal sent a text confessing to Andie's murder and killed himself. But questions about the case have always lingered and smart and single-minded Pip is convinced of Sal's innocence. Now she's going to prove it. Teaming up with Sal's brother Ravi, Pip questions old friends and follows long-buried leads. It isn't long before the two discover shaky alibis and sordid secrets. The town is on edge. Pip is in danger. And time is running out.